Preventable hospitalizations through ED: does the number of hospital beds matter under the global budget in a single-payer system in Taiwan? - Chen, Hsueh-Fen; Hsieh, Hui-Min; Chang, Wei-Shan (Frontiers in Public Health, 2025)
BackgroundTaiwan implemented global hospital budgeting with a floating-point value, which created a prisoner's dilemma. As a result, hospitals increased service volume, which caused the floating-point value to drop to less than one New Taiwan Dollar (NTD). The recent increase in the number of hospital beds and the call to enhance the floating-point value to one NTD raise concerns about the potential for increased financial burden without adding value to patient care if hospitals expand their bed capacity for volume-based competition. The present study aimed to examine the relationship between the supply of hospital beds and hospitalizations following an emergency department (ED) visit (called ED hospitalizations) by using diabetes-related ambulatory care sensitive conditions (ACSCs) that are preventable and discretionary as an example.MethodsThe study was a pooled cross-sectional design analyzing 2011–2015 population-based claims data in Taiwan. The dependent variable was a dummy variable representing an ED hospitalization, with a treat-and-leave ED visit as the reference group. The key independent variable is the number of hospital beds per 1,000 populations. Multivariate logistic regression models with and without a clustering function were used for the analyses.ResultsApproximately 59.26% of diabetes-related ACSCs ED visits resulted in ED hospitalizations. The relationship between the supply of hospital beds and ED hospitalizations was statistically significant (OR = 1.12; 95% CI: 1.09–1.14; P < 0.001) in the model without clustering but was statistically insignificant in the model with clustering (OR = 1.03; 95% CI: 0.94–1.12; P > 0.05). Several social risk factors were positively associated with the likelihood of ED hospitalizations, such as low income and the percentage of the population without a high school diploma. In contrast, other factors, such as female patients and the Charlson comorbidity index, were negatively associated with the likelihood of ED hospitalizations.ConclusionUnder hospital global budgeting with a floating-point value mechanism, increases in hospital beds likely motivate hospitals to admit ED patients with preventable and discretionary conditions. Our study emphasizes the urgent need to add value-based incentive mechanisms to the current global budget payment. The value-based incentive mechanisms may encourage providers to focus on quality of patient care by addressing social risk factors rather than engage in volume-based competition, which would improve population health while reducing preventable ED visits and hospitalizations.